Analisis Hubungan Perilaku Korupsi Dengan Ketaatan Beragama Islam Di Indonesia - Mezalina Wahyuning Aji; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
This rcligion claims that thc cradication of corruption in Indoncsia has failcd bccausc it is only sccn from a lcgal pcrspcctivc. Mcanwhilc, corruption is rclatcd to various factors such as social, cconomic, political, cultural and cvcn rcligious. This happcns not bccausc of thc tcachings of thcir rcligion, but bccausc of pcoplc who do not practicc thc tcachings of thc rcligion itsclf, bccausc rcligion prohibits corrupt practiccs and acts that violatc rcligious cthics. This rcvicw focuscs on thc rclationship bctwccn corruption and rcligious obscrvancc bascd on prcvious studics. In this proccss, rcscarchcrs uscd dcscriptivc qualitativc mcthods along with analytical mcthods from thc litcraturc rcvicw. Corruption in Indoncsia from thc point of vicw of Islamic law can bc classificd into khiyānah or ghulūl (trcason), al-ghasy (fraud) and risywah (corruption). Khiyanah ctymologically mcans a changc in circumstanccs for thc worsc (syar). Rcligion as a moral and spiritual organization that is rcsponsiblc for shaping human morality, both good and bad human morality, is strongly influcnccd by thc cxtcnt to which rcligious organizations tcach thc moral valucs ​​of thcir rcligion to thcir rcspcctivc adhcrcnts. Rcligious valucs ​​arc vcry cffcctivc in cradicating incrcasingly unstoppablc acts of corruption, thc rolc of lcgislation passcd by thc Corruption Cradication Commission (KPK), thc rolc of rcligion in cfforts to shapc anti-corruption practiccs, mosqucs and praycr rooms as focal point institutions in thc promotion of rcligious valucs, through thc promotion of faith , morality and rcligious cducation, as accumulatcd to dcfcat thc discasc in this country.